Examining the impact of the various dimensions of employees’ engagement on commitment: Evidence from small and medium enterprises in Egypt - Mohamed Mostafa Saad; Hazem R. Abdelwakeel; Ashraf A. Labib (SA Journal of Human Resource Management, 2022)
Orientation: With the intense competition that many organisations are facing, they are looking for new ways to enhance employees’ engagement and commitment.